2010
DOI: 10.1177/0963721410377599
|View full text |Cite
|
Sign up to set email alerts
|

Emotion in Schizophrenia

Abstract: Our understanding of the nature of emotional difficulties in schizophrenia has been greatly enhanced by translational research over the past two decades. By incorporating methods and theories from affective science, researchers have been able to discover that people with schizophrenia exhibit very few outward displays of emotion but report experiencing strong feelings in the presence of emotionally evocative stimuli or events. Recent behavioral, psychophysiological, and brain imaging research has pointed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(70 citation statements)
references
References 20 publications
4
66
0
Order By: Relevance
“…Indeed, we have argued for and demonstrated anticipatory pleasure deficits in schizophrenia (Barch and Dowd, 2010; Dowd and Barch, 2010, 2012; Gard et al, 2007; Kring and Caponigro, 2010; Wynn et al, 2010). In the animal literature, anticipatory pleasure has been characterized as “wanting” and distinguished from “liking” or in-the-moment pleasure experience (Berridge, 2004; Berridge and Robinson, 1998).…”
Section: Anticipatory Pleasurementioning
confidence: 86%
See 1 more Smart Citation
“…Indeed, we have argued for and demonstrated anticipatory pleasure deficits in schizophrenia (Barch and Dowd, 2010; Dowd and Barch, 2010, 2012; Gard et al, 2007; Kring and Caponigro, 2010; Wynn et al, 2010). In the animal literature, anticipatory pleasure has been characterized as “wanting” and distinguished from “liking” or in-the-moment pleasure experience (Berridge, 2004; Berridge and Robinson, 1998).…”
Section: Anticipatory Pleasurementioning
confidence: 86%
“…Thus, when we predict whether or not we will enjoy the latest novel by a favorite author, we likely draw upon our past experiences with the authors’ novels to guide our predictions. Maintaining emotional experiences as they occur likely facilitates the development of memories for these experiences (Kring and Caponigro, 2010). There is a very robust literature suggesting that people with schizophrenia have deficits in active maintenance of non-emotional information in working memory, with a number of meta-analyses summarizing this evidence (Forbes et al, 2009b; Lee and Park, 2005).…”
Section: Maintenance Integration and Updatingmentioning
confidence: 99%
“…The choice to engage in affiliative behavior may in part be derived from the individual's expectation or experience of pleasure or reward from the social encounter. Laboratory evocative studies would suggest that hedonic responding is intact in schizophrenia (Cohen and Minor, 2010; Kring and Caponigro, 2010; Kring and Elis, 2013). However, caution is appropriate in extrapolating from these laboratory studies to affiliative interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been suggested that whereas reward receipt may only be subtly affected in both disorders (Cohen and Minor, 2010;Arrondo et al, 2015), the anticipation of reward (Juckel et al, 2006b;Sherdell et al, 2012) and its motivational aspects (e.g., the effort that a subject is willing to make to get it) Barch et al, 2014;Gard et al, 2014) may be markedly dysfunctional in schizophrenia and in depression (for in-depth reviews of the issue see Barch and Dowd, 2010;Kring and Caponigro, 2010;DerAvakian and Markou, 2012;Argyropoulos and Nutt, 2013;Kring and Barch, 2014;. Abnormalities in reward prediction error signaling in the striatum in schizophrenia are also a well-known finding that could be involved in the pathogenesis of psychotic symptoms Ziauddeen and Murray, 2010).…”
Section: Abstract: Reward System Ventral Striatum Monetary Incentivmentioning
confidence: 99%